“QUIERO QUE LA GIMNÁSTICA TOME BASTANTE INCREMENTO”: LOS ORÍGENES DE LA GIMNASIA COMO ACTIVIDAD FÍSICA EN COSTA RICA (1855-1949) - Díaz Bolaños, Ronald E (2011)
The article analyzes the historical processes leading to the development of gymnastics in Costa Rica as physical activity since the mid-nineteenth century until the 1940’s. The research points out the role of gymnastics in the curriculum of secondary schools and the creation of private groups that promoted the teaching of this activity throughout the study period.